REVITALISASI USAHA KECIL MENENGAH DHARMA BOGA BOJONEGORO MELALUI PELATIHAN CARA PRODUKSI DAN REGISTRASI PANGAN YANG BAIK SERTA HALAL - Isnaeni,; Nasution, Noor Erma; Sugijanto,; Poerwono, Hadi; Ekowati, Juni; Siswandono,; Rudyanto, Marcellino; Nofianti, Kholis Amalia; Syahrani, Achmad; Suzana, (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. The independence of food supply in Indonesia is supported by the abundant diversity of natural ingredients from vegetable, animal and mineral sources. Compared to drugs, dependence on food products in other countries is relatively lower, because the fabrication requires facilities and infrastructure that can be fulfilled domestically. The regulatory system managed by the Republic of Indonesia Drug and Food Control Agency (BPOM-RI) has been implemented to ensure that food products consumed by the public are of high quality, nutritious, safe, halal, and affordable and with a taste that satisfies user communities. Circular-worthy products must at least meet the registration requirements of halal aspects, maximum microbial limits and chemical contamination. The growth of Micro, Small and Medium Enterprises (MSMEs) is also facilitated by the government. Dharma Boga is one of the Small and Medium Enterprises (UKM) in Klangon sub-district, Bojonegoro which is engaged in food production for more than 10 years. Some problems related to registration, halal certification and handling of production, especially food additives that meet requirements, has been communicated to the Community Service Team (PENMAS) Faculty of Pharmacy, Airlangga University (FFUA). Alhamdulillah, PENMAS activities with training materials on how to produce and register good and halal food have been carried out with satisfactory results, although it still needs to be followed up with a partnership for the MSME revitalization program in the future. Of the three parameters used to measure participants' understanding of training material, the average obtained more than 30% showed an increase. For the introduction of the halal logo and the dangers of formaldehyde, 100% of the message is understood. The training involved experts and stakeholders in the authority of the East Java Indonesian Ulama Council and the teaching staff and the Airlangga University Faculty of Pharmacy Testing Service Unit. Abstrak. Kemandirian penyediaan pangan di Indonesia didukung oleh diversitas bahan alam yang melimpah baik dari sumber nabati, hewani, maupun mineral. Dibandingkan obat, ketergantungan produk pangan pada negara lain relatif lebih rendah, karena fabrikasinya membutuhkan fasilitas dan infrastruktur yang dapat terpenuhi di dalam negeri. Sistem regulasi yang dikelola oleh Badan Pengawas Obat dan Makanan Republik Indonesia (BPOM-RI) telah diberlakukan untuk menjamin produk makanan yang dikonsumsi masyarakat berkualitas, bergizi, aman, halal, dan terjangkau serta dengan rasa yang memuaskan selera masyarakat. Produk yang laik edar minimal harus memenuhi persyaratan registrasi dari aspek halal, batas maksimum mikroba dan cemaran bahan kimia. Tumbuh kembangnya Usaha Mikro, Kecil dan Menengah (UMKM) juga difasilitasi oleh pemerintah. Dharma Boga adalah salah satu Usaha Kecil Menengah (UKM) di kecamatan Klangon, Bojonegoro yang bergerak dibidang produksi makanan selama lebih dari 10 tahun. Beberapa permasalahan terkait registrasi, sertifikasi halal dan penanganan produksi terutama bahan tambahan makanan yang memenuhi persyaratan, telah dikomunikasikan kepada Tim Pengabdian kepada Masyarakat (PENMAS) Fakultas Farmasi Univeritas Airlangga (FFUA). Alhamdulillah kegiatan PENMAS dengan materi pelatihan cara produksi dan registrasi pangan yang baik serta halal telah dilaksanakan dengan hasil yang memuaskan, walaupun masih perlu ditindaklanjuti dengan jalinan kerjasama untuk program revitalisasi UMKM di masa mendatang. Dari tiga parameter yang digunakan untuk mengukur pemahaman peserta terhadap materi pelatihan, rerata yang diperoleh lebih dari 30% menunjukkan peningkatan. Untuk pengenalan logo halal dan bahaya formalin, 100% peserta sudah paham. Pelatihan melibatkan pakar dan pemangku kewenangan dari Majelis Ulama Indonesia Jawa Timur dan para staf pengajar serta Unit Layanan Pengujian Fakultas Farmasi Universitas Airlangga.